Strategic Planning Model for Islamic-Based Elementary School Development: Model Perencanaan Strategis Pengembangan Sekolah Dasar Berbasis Islam - haqiqi, M. Natsar; Wahyuni, Hana Catur (Indonesian Journal of Education Methods Development, 2025)
General background: The transformation of primary education institutions in Indonesia is crucial to improving educational quality and competitiveness. Specific background: SD Muhammadiyah 10 Balongbendo seeks to enhance its institutional performance through long-term strategic planning aligned with Islamic values and national education standards. Knowledge gap: However, there is a lack of structured and measurable development frameworks that integrate religious, academic, and technological domains in Islamic elementary schools. Aims: This study aims to formulate a comprehensive Master Plan for the Development of SD Muhammadiyah 10 Balongbendo for the period 2024–2036, grounded in SWOT analysis and participatory planning. Results: The findings include a structured four-phase development roadmap targeting improved governance, educational excellence, and national recognition. The formulation process involved stakeholders such as school leaders, teachers, the foundation, and the school committee. Novelty: The proposed model uniquely integrates Islamic education (ISMUBA), environmental awareness, digital literacy, and character building within a holistic development framework. Implications: This master plan offers a replicable model for strategic development in Islamic primary schools, supporting national efforts to achieve educational equity and quality. Highlights :  Integrates Islamic values with academic and technological goals. Uses participatory SWOT-based strategic planning. Provides a replicable model for Islamic school development. Keywords: Strategic Planning, Islamic Education, Elementary School, SWOT Analysis, School Development